Retoryka mediów wobec zagadnienia Deportacji Akadian na przykładzie wybranych artykułów z "La Presse i Le Journal de Montréal" - Zacharow, Sebastian (Acta Neophilologica, 2021)
The purpose of this article is to demonstrate, based on the example of two Canadian journals, how memory remains alive after the events of 1755, when the deportation of the Acadians took place. In spite of the 250 years which have passed since the event, the French-language press in Canada remains extremely sensitive to the topic of the expulsion of the French from New Brunswick and Nova Scotia by the British, and it frequently expresses its attachment to the memory of the Acadians.